2013
DOI: 10.1523/jneurosci.0447-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Error-Monitoring and Post-Error Compensations: Dissociation between Perceptual Failures and Motor Errors with and without Awareness

Abstract: Whether humans adjust their behavior in response to unaware errors remains a controversial issue relevant to insight in neuropsychiatric conditions. Initial error awareness studies found that the error-related negativity (ERN), an event-related potential (ERP) originating in the medial prefrontal cortex after errors, activated equally for aware and unaware errors, suggesting a candidate preconscious mechanism. However, recent studies demonstrate that the ERN decreases after unaware errors. We hypothesized that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
64
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 57 publications
(22 reference statements)
5
64
1
Order By: Relevance
“…Hewig et al, 2011;Navarro-Cebrian & Kayser, 2013;Roger, Benar, Vidal, Hasbroucq, & Burle, 2010;Scheffers & Coles, 2000;Shalgi & Deouell, 2012;Wessel, Danielmeier, Morton, & Ullsperger, 2012), it contradicts the traditional view that ERN is related to implicit but not to explicit error awareness (e.g. Ehlis, Herrmann, Bernhard, & Fallgatter, 2005;Endrass et al, 2005Endrass et al, , 2007Hester, Foxe, Molholm, Shpaner, & Garavana, 2005;Hughes & Yeung, 2011;Nieuwenhuis et al, 2001;O'Connell et al, 2007;Overbeek et al, 2005;Steinhauser & Yeung, 2010).…”
Section: Discussionmentioning
confidence: 90%
“…Hewig et al, 2011;Navarro-Cebrian & Kayser, 2013;Roger, Benar, Vidal, Hasbroucq, & Burle, 2010;Scheffers & Coles, 2000;Shalgi & Deouell, 2012;Wessel, Danielmeier, Morton, & Ullsperger, 2012), it contradicts the traditional view that ERN is related to implicit but not to explicit error awareness (e.g. Ehlis, Herrmann, Bernhard, & Fallgatter, 2005;Endrass et al, 2005Endrass et al, , 2007Hester, Foxe, Molholm, Shpaner, & Garavana, 2005;Hughes & Yeung, 2011;Nieuwenhuis et al, 2001;O'Connell et al, 2007;Overbeek et al, 2005;Steinhauser & Yeung, 2010).…”
Section: Discussionmentioning
confidence: 90%
“…Although both the ERN and the Pe are modulated by error awareness, the Pe awareness effect has been suggested to reflect a more binary decision (i.e., error or correct) regarding the error whereas the magnitude of the ERN is more sensitive to the subjective level of confidence that an error was committed (Navarro-Cebrian, Knight, & Kayser, 2013; Shalgi & Deouell, 2012). Dipole source localization indicated that the Pe had generators in the posterior cingulate cortex (PCC; see also O’Connell et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…An important question is whether awareness is necessary to elicit post-error behavioral adjustments (Navarro-Cebrian, Knight, and Kayser, 2013). The literature on this issue comprises several contributions, especially from the field of the neurosciences (Wessel, 2012).…”
mentioning
confidence: 99%